Management of Education Financing Management at Madrasah Aliyah - Hakimah, Milatul; Asy’ari, Hasyim; Muslihun (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study applies a qualitative research method with a case study approach at MA Hasanatul Huda in Sumedang. Data were collected through observation, interviews, and documentation, involving various parties such as the foundation chairman, headmaster, vice headmaster for student affairs, committee members, teachers, laboratory head, and administrative staff. Data analysis was conducted through data collection, reduction, presentation, and conclusion drawing. Data validity was examined through source triangulation. The analysis results conclude that educational financing planning is carried out through activity inventory, financing sources, and RKAM preparation. Financing implementation is divided into expenditure and financial accounting. Supervision is conducted internally by the school principal, committee, and foundation, and externally by the Ministry of Religious Affairs of Sumedang Regency and the Directorate General of the Ministry of Religious Affairs of the Republic of Indonesia, using methods of inspection, monitoring, research, supervision, and reporting to ensure that budget utilization aligns with plans and the effectiveness of educational programs.